2020
DOI: 10.3390/f11121249
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Oak Bark Powder as a Filler for Melamine-Urea-Formaldehyde Adhesive in Plywood Manufacturing

Abstract: The woodworking industry generates a great amount of bark which has not yet found a wider industrial application. None of the previously conducted research has considered oak bark application (which is one of the most often processed wood species in Poland) as a filler for wood adhesives. Moreover, no studies have determined the properties of bark containing melamine-urea-formaldehyde resin (MUF), which increasingly replaces pure urea-formaldehyde adhesives. Thus, the aim of the study was to determine the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…It was also pointed out that the addition of extra 10% of WF in Ref20 compared to Ref10 sample led to slight increase of formaldehyde release (3%). The specific chemical composition of BB in the UF adhesive mixture apparently affected the mechanical properties of plywood to a minimal extent which is also supported by other research works [19,20,31].…”
Section: Formaldehyde Emission From Plywood Panelssupporting
confidence: 80%
See 3 more Smart Citations
“…It was also pointed out that the addition of extra 10% of WF in Ref20 compared to Ref10 sample led to slight increase of formaldehyde release (3%). The specific chemical composition of BB in the UF adhesive mixture apparently affected the mechanical properties of plywood to a minimal extent which is also supported by other research works [19,20,31].…”
Section: Formaldehyde Emission From Plywood Panelssupporting
confidence: 80%
“…Results showed that use of 20% BB leads to a 17% decrease in formaldehyde release. The same authors [31] used oak bark powder as filler for MUF adhesive in plywood manufacturing. The formaldehyde emissions, measured initially and after 8 weeks, experienced a 9% and 31% decrease in comparison with the reference variant, As seen in Figure 2, a significantly greater decrease in formaldehyde emission of plywood samples, comprising BB as a filler was measured after four weeks, compared to the tested WF reference samples.…”
Section: Formaldehyde Emission From Plywood Panelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, the formaldehyde limit values have steadily been lowered, which has led to the development of less toxic, low-emission, eco-friendly, wood-based panels, where conventional synthetic resins have been partially or completely replaced by sustainable, bio-based adhesives [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] or by adding formaldehyde scavengers to adhesive formulations, such as urea [ 48 ], sodium metabisulfite (Na 2 S 2 O 5 ), ammonium bisulfite ((NH 4 )HSO 3 ), other ammonium-containing agents [ 49 , 50 ], Al 2 O 3 nanoparticles [ 51 ], etc. Various natural compounds, such as wood bark flours [ 32 , 52 , 53 , 54 ] and tannins [ 55 , 56 , 57 ], have also been successfully used to reduce the free formaldehyde content of wood panels.…”
Section: Introductionmentioning
confidence: 99%